Director’s Perceived Competition and Its Relationship with Hospital’s Competitive Behaviors: Evidence from County Hospitals in China - Zhou T; Yang Y; Hu M; Jian W; Pan J (Dove Medical Press, 2021)
Tingting Zhou,1,2 Yili Yang,2 Min Hu,3 Weiyan Jian,4 Jay Pan1,2 1HEOA Group, West China School of Public Health and West China Fourth Hospital, Sichuan University, Chengdu, People's Republic of China; 2Institute for Healthy Cities and West China Research Center for Rural Health Development, Sichuan University, Chengdu, People's Republic of China; 3School of Public Health, Fudan University, Shanghai, People's Republic of China; 4Department of Health Policy and Management, School of Public Health, Peking University Health Science Center, Beijing, People's Republic of ChinaCorrespondence: Jay PanHEOA Group, West China School of Public Health and West China Fourth Hospital, Sichuan University, No. 17, Section 3, Ren Min Nan Road, Chengdu, Sichuan, 610041, People's Republic of ChinaEmail panjie.jay@scu.edu.cnBackground: This study was conducted for assessing the degrees of perceived competition reported by county hospital directors in rural China as well as hospitals' competitive behaviors in response to competition.Methods: The data were collected from Analysis of Provider Payment Reforms on Advancing China's Health (APPROACH) project which had been implemented among county hospitals in China's Guizhou province. Competition was measured by asking hospital directors to rate the levels of competitive pressure as they perceived. Hospitals' competitive behaviors were obtained by asking hospitals' directors about specific strategies they had adopted. A multivariable linear regression model was developed to examine the relationship between perceived competition and the positivity of competitive behavior, and multivariable logistic regressions were used to evaluate the influence of perceived competition on the adoption of specific competitive strategies.Results: Among 218 directors engaged in this study, 210 (96.3%) directors reported the perception of certain degrees of competition, for which the competitive pressure was mainly posed by public hospitals (42.4%). Director-perceived competition level was found to be positively associated with the positivity of competitive behavior, and directors under higher competitive pressure were found to be more likely to adopt multiple competitive strategies including improving the efficiency of hospitals' internal management, optimizing hospitals' environment as well as promoting health-care services.Conclusion: This study suggested that almost all of the county hospital directors in rural China perceived certain degrees of competitive pressure, and higher levels of perceived competition were found to be significantly associated with increased positivity in adopting competitive strategies. Our findings are expected to provide evidence-based implications for the implementation of a series of pro-competition policies throughout health-care reforms.Keywords: perceived competition, hospital behavior, county hospital, director, China